Hybrid robo-advisory services for Islamic financial institutions - Adam Sa'ad, Auwal (2020)
The robo-advisory services introduction for Shariah-related Fatwas is to innovate a hybrid Shariah advisory system that may simplify the rigorous processes and duties of Shariah advisors. Robo-advisory services may serve as a mechanism to assisting Shariah advisors in executing their Shariah advisory services using modern technology. ASST PROF DR AUWAL ADAM SA’AD provides an insight on why Islamic fi nancial institutions as well as relevant Islamic fi nancial regulators should leverage on this ongoing crusade of robo-advisors to eff ectively enhance Shariah advisory services.